iGenetics a molecular approach - Russell, Peter J. (San Francisco Benjamin Cummings, 2010)
With its modern chapter organization and new Focus on Genomics boxes, iGenetics: A Molecular Approach reflects the increasing molecular emphasis in todays experimental study of genes while helping students develop problem-solving skills and an appreciation for classic experiments. Although molecular topics are presented first, instructors can assign the chapters in any sequence. Pedagogical features such as chapter-opening Key Questions and strategically placed Keynotes help students to efficiently master genetic concepts. The Genetics Place Companion Website contains interactive iActivities and narrated animations that help students visualize and understand processes and concepts that are illustrated in the text.
1. Genetics: An Introduction 2. DNA: The Genetic Material 3. DNA Replication 4. Gene Control of Proteins 5. Gene Expression: Transcription 6. Gene Expression: Translation 7. DNA Mutation, DNA Repair, and Transposable Elements 8. Genomics 9. Functional and Comparative Genomics 10. Recombinant DNA Technology 11. Mendelian Genetics 12. Chromosomal Basis of Inheritance 13. Extensions of and Deviations from Mendelian Genetic Principles 14. Genetic Mapping in Eukaryotes 15. Genetics of Bacteria and Bacteriophages 16. Variations in Chromosome Structure and Number 17. Regulation of Gene Expression in Bacteria and Bacteriophages 18. Regulation of Gene Expression in Eukaryotes 19. Genetic Analysis of Development 20. Genetics of Cancer 21. Quantitative Genetics 22. Population Genetics 23. Molecular Evolution.
Includes bibliographical references (p. 728-741) and index.
Keywords: Molecular genetics